PELAKSANAAN PERJANJIAN PEMBERIAN KREDIT PADA USAHA EKONOMI DESA SIMPAN PINJAM DI DESA ANGKASA KECAMATAN BANDAR PETALANGAN - Sukma Apyanda; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Economic Enterprises-Village Savings and Loans hereinafter called UED-SP, the Village Empowerment Program (PPD), which made the Central Government to improve the economies of rural communities. Legal Basis On UED-SP is set on Government Affairs Regulation No. 6 of 1998 on Rural Economic Enterprises - Savings and Loans. Minister Regulation No. 6 of 1998 on Rural Economic Enterprises - Savings and Loans provide an understanding UED-SP is an institution engaged in the field of savings and loans and is owned by the village community / village cultivated and managed by village communities / villages.The aim of this thesis to determine the cause of the debtor in default on UED-SP Taskin Space as well as to determine the completion of the problems for debtors who are in default on UED-SP Taskin Angkasa.Jenis research that will be used is the sociological research, sociological research is research that examines aspects legal to look at legislation in force and compares with the implementation on the ground by means of a survey. The location study was conducted in UED-SP Taskin held at Desa Angkasa District of Bandar Petalangan Pelalawan. Characteristically research descriptive. The data source is the legal data on the use of primary, secondary and tertiary.It can be concluded, Factor causes of bad loans in UED-SP Taskin Space writer get consists of the following: factors derived from the UED-SP (Management and Authority), First, business less careful in analyzing the debtor's credit request. Second, the excessive extension of credit (over financing) on the needs of the debtor. Third, lack of supervision on loans. The next factor is derived from the internal debtors: First, Customer misuse of credit. Second, the customer is less able to manage their business. Third, the customer bad faith. And external factors beyond the ability UED-SP and the debtor: First, natural disasters. Second, Termination (PHK). Third, The decline in selling prices of agricultural products. While the completion of the problems for debtors who are in default on UED-SP Taskin Space never seizure and sale of collateral debtors. It is based on the decision of the village consultation meetings. Following the completion of the problems of the borrowers who are in default: First, the decrease in Interest Rate. Second, the extension of credit period. Third, Sales part or all of the guarantee by the debtor. Fourth, the Sale of Goods Warranty conducted by UED-SP Taskin Space. UED-SP Taskin Space does not conduct auctions for debtors that do arrears which has been given a subpoena by 2 times, this policy is decided by consensus Village for certain considerations.Keywords: Implementation Agreements, credit freeze and UED-SP.